2001
DOI: 10.1089/104303401300057405
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Plasmid DNA to Hepatotoxicity after Systemic Administration of Lipoplexes

Abstract: Several studies have demonstrated that intravenous administration of DNA complexed with cationic lipid vectors induces the production of large quantities of proinflammatory cytokines. In this study we confirm these observations, using cationic lipid DOTAP and cationic phospholipid compounds. Moreover, we demonstrate that although intravenous administration of lipid-DNA complexes does not induce toxic effects in the lung, high transgene expression in lung correlates with histopathological lesions in liver, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 23 publications
1
49
0
1
Order By: Relevance
“…Animals that survive this initial shock eventually succumb from continued lung reaction and mounting liver toxicity. 9,41 These later toxic effects may be mediated through the same blood effects but also via activation of macrophages and other non-parenchymal cells in these organs (in particular Kupffer cells) after uptake of large amounts of cationic DNA complexes. 9 The importance of CpG DNA sequences lends credence to the role of DNA uptake in the systemic toxicity of cationic DNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Animals that survive this initial shock eventually succumb from continued lung reaction and mounting liver toxicity. 9,41 These later toxic effects may be mediated through the same blood effects but also via activation of macrophages and other non-parenchymal cells in these organs (in particular Kupffer cells) after uptake of large amounts of cationic DNA complexes. 9 The importance of CpG DNA sequences lends credence to the role of DNA uptake in the systemic toxicity of cationic DNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically administered plasmid vectors can also induce hepatotoxicity and both humoral and cell-mediated immune responses that limit their application in vivo, an effect most frequently observed when viral promoters such as CMV are used to drive transgene expression [Loisel et al, 2001;Tousignant et al, 2000]. Studies have indicated that inflammation associated with plasmid DNA may be due to the presence of particular unmethylated C⋅G dinucleotides ('CpG-S DNA') (reviewed in [Krieg, 1999]).…”
Section: Viral Promoters In Plasmid Vectorsmentioning
confidence: 99%
“…3 Moreover, the intravenous injection of cationic liposome/pDNA complexes causes proinflammatory cytokine-induced hepatic toxicity because of the recognition of Toll-like receptor 9 to CpG motifs in the pDNA sequence that upregulate the activation of transcription factors, such as nuclear factor-kB (NF-kB), thereby contributing to the production of proinflammatory cytokines from liver macrophages. [4][5][6][7][8] Therefore, an approach to enhance the antitumor efficacy and reduce the toxicity of cationic liposome/IL-12 pDNA complexes for treatment of metastatic lung tumors is required. Combination therapy has been used to increase the antitumor efficacy and reduce the systemic toxicity of IL-12.…”
Section: Introductionmentioning
confidence: 99%